Venous thromboembolism incidence and risk factors in non-small cell lung cancer patients receiving first-line systemic therapy. Issue 208 (December 2021) - Hill, Hailey; Robinson, Myra; Lu, Lauren; Slaughter, Daniel; Amin, Asim; Mileham, Kathryn; Patel, Jai N.
Abstract: Background: There are limited data on venous thromboembolism (VTE) incidence and predictive factors in non-small cell lung cancer (NSCLC) across first-line therapies. Objective: To evaluate VTE incidence rates and identify predictive factors in NSCLC patients receiving first-line systemic therapies, including immune checkpoint inhibitors (ICIs). Patients/methods: This is a single institution retrospective study of adult NSCLC patients who received first-line treatment, including chemotherapy, ICIs (pembrolizumab, nivolumab, atezolizumab, avelumab, and durvalumab), and/or targeted therapies (TTs) (erlotinib, gefitinib, afatinib, osimertinib, crizotinib, alectinib, ceritinib). Risk factors included Khorana score, cancer stage, central venous catheter, pacemaker, comorbidities, and prior VTE. The primary objective - cumulative incidence of VTE at 6- and 12-months by treatment group – was compared using Gray's test. Univariable and multivariable competing risk analyses were used to identify predictors. Results: Of 1587 evaluable patients, 53% were male, 79% white, 18% black, median age was 66; 58% had adenocarcinoma, 32% squamous cell carcinoma, and 47% metastatic disease; 1043 received chemotherapy, 171 ICIs, 157 chemotherapy plus concomitant ICI, 107 chemotherapy and durvalumab maintenance, and 109 TTs. The 6-month cumulative incidence of VTE by treatment type was 5.0%, 7.6%, 9.9%, 9.4%, and 11.1%; 12-month incidence was 6.5%, 9.0%, 12.8%, 12.2%, and 13.1% per arm, respectively ( p  = 0.01). Treatment type ( p  = 0.034) and nicotine dependence ( p  = 0.048) were significantly associated with time to VTE in multivariable analyses. Conclusion: Treatment type and smoking status were predictive of time to VTE in NSCLC patients receiving various first-line therapies. Cumulative incidence was highest in those receiving TTs and combination chemotherapy plus ICI. Highlights: Lung cancer patients receiving targeted therapies had the highest thrombosis rate. Patients receiving immunotherapies plus chemotherapy also had higher thrombosis rates. Smoking status was associated with incidence of thrombosis in lung cancer patients.